Kinetic Degradation and colour stability in an aqueous system of spray-dried metal-stabilised amaranth powder encapsulated in different wall materials - Siti Faridah Mohd Amin; Kharidah Muhammad; Yus Aniza Yusof; Ahmad Hazim Abdul Aziz; Nor Qhairul Izzreen Mohd Noor (Penerbit UTM Press, 2025)
The present study aims to determine the kinetics of chlorophyll degradation and green colour stability of encapsulated copper (Cu)- and zinc (Zn)-amaranth powders stored under accelerated (45°C) and room (25°C) temperature for 16 weeks and six months, respectively. The powders were spray-dried using 10% maltodextrin (DE 10), resistant maltodextrin, N-Octenyl Succinate Anhydride starches (HI-CAP® 100 and CAPSUL®), and gum Arabic (GA). The effects of pH (4 to 8, in the absence of light at 25°C for 24 hours), temperature (40 to 100°C for 90 mins), and light exposure (fluorescent light at 25°C for five days) on the chlorophyll retention and colour stability of the powders in an aqueous system were also explored. The chlorophyll degradation kinetics of the powders followed a first-order reaction model. The Zn-amaranth powder encapsulated with CAPSUL® exhibited the lowest rate constant (k = 2.7 × 10−3 weeks−1) and the highest half-life (t1/2 = 256.72 weeks) under storage at 25°C. The Cu-amaranth powder encapsulated with GA demonstrated the highest greenness value during storage at both 25°C (six months) and 45°C (16 weeks). In the aqueous system, the Cu-amaranth powder encapsulated with GA possessed the highest chlorophyll retention (> 90%) in acidic conditions. Meanwhile, maltodextrin-encapsulated Cu-amaranth powder exhibited better chlorophyll retention and colour stability under light exposure and high temperatures.